2021
DOI: 10.1371/journal.pone.0253849
|View full text |Cite
|
Sign up to set email alerts
|

In vivo mitochondrial ATP production is improved in older adult skeletal muscle after a single dose of elamipretide in a randomized trial

Abstract: Background Loss of mitochondrial function contributes to fatigue, exercise intolerance and muscle weakness, and is a key factor in the disability that develops with age and a wide variety of chronic disorders. Here, we describe the impact of a first-in-class cardiolipin-binding compound that is targeted to mitochondria and improves oxidative phosphorylation capacity (Elamipretide, ELAM) in a randomized, double-blind, placebo-controlled clinical trial. Methods Non-invasive magnetic resonance and optical spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Elam also had a positive effect on physical performance, increasing age-related muscle strength and agility, as shown by grip strength and rotarod data. This is supported by several studies as Elam is known to counter age-related muscle fatigue and reverse the mitochondrial deficits of ATP production in skeletal muscle [3]. Interestingly, our data only supports this for male mice, with no difference in physical performance between Elam and control-treated female mice; even though Elam has been shown in past studies to improve exercise tolerance in females as well as males [9,21].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Elam also had a positive effect on physical performance, increasing age-related muscle strength and agility, as shown by grip strength and rotarod data. This is supported by several studies as Elam is known to counter age-related muscle fatigue and reverse the mitochondrial deficits of ATP production in skeletal muscle [3]. Interestingly, our data only supports this for male mice, with no difference in physical performance between Elam and control-treated female mice; even though Elam has been shown in past studies to improve exercise tolerance in females as well as males [9,21].…”
Section: Discussionsupporting
confidence: 84%
“…Enhancing mitochondrial function can delay or reverse some of the untoward effects of aging by targeting metabolic and bioenergetic processes [1,2,3]. Several reports have focused on mitochondrial-targeted catalase, a reac-tive oxygen species (ROS) scavenger that was found to be protective of a number of aging phenotypes [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…To test whether PD was associated with mitochondrial dysfunction in the skeletal muscle the ATPmax was assessed in the FDI and TA muscles in the PD subjects and compared with data from healthy age-matched controls from previously published clinical trials [ 31 , 32 , 33 ]. In the TA, the ATPmax was significantly reduced in the PD subjects relative to the control group ( Figure 2 A, Table 2 ), while there was no difference in ATPmax in the FDI between the PD and control subject groups ( Figure 2 B, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…All study procedures took place at the Translational Bioenergetics Laboratory (TBL) human research lab in the UW Department of Radiology in Seattle, WA, USA. Control data from healthy age-matched subjects were collected between 2014–2021 during three previous clinical trials related to MRS muscle metabolomics at the UW Department of Radiology [ 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies have demonstrated the ability of SS-31 to maintain cellular bioenergetics under stress conditions such as ischemia, hypoxia, and aging-related dysfunction ( Allen et al, 2020 ; Campbell et al, 2019 ; Szeto, 2018 ; Zhang et al, 2020 ). The clinical efficacy of SS-31 has been demonstrated for primary mitochondrial disorders ( Zhao et al, 2017 ; Reid Thompson et al, 2021 ) and for age-related chronic diseases associated with mitochondrial dysfunction ( Roshanravan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%